2016
DOI: 10.1175/mwr-d-15-0255.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of a Cumulus Parameterization Scheme to Precipitation Production Representation and Its Impact on a Heavy Rain Event over Korea

Abstract: The sensitivity of a cumulus parameterization scheme (CPS) to a representation of precipitation production is examined. To do this, the parameter that determines the fraction of cloud condensate converted to precipitation in the simplified Arakawa–Schubert (SAS) convection scheme is modified following the results from a cloud-resolving simulation. While the original conversion parameter is assumed to be constant, the revised parameter includes a temperature dependency above the freezing level, which leads to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Previous studies (e.g. Han et al., ; Van Weverberg et al., ) have shown that parameterization schemes on convection, subgrid‐scale cloud microphysical process of the convective clouds and resultant precipitation all can affect the convergence/divergence in models. Recent study by Sandu et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (e.g. Han et al., ; Van Weverberg et al., ) have shown that parameterization schemes on convection, subgrid‐scale cloud microphysical process of the convective clouds and resultant precipitation all can affect the convergence/divergence in models. Recent study by Sandu et al.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Previous studies (e.g. Han et al, 2016;Van Weverberg et al, 2012) have shown that parameterization schemes on convection, subgrid-scale cloud microphysical process of the convective clouds and resultant precipitation all can affect the convergence/divergence in models. Recent study by Sandu et al (2019) suggests that parameterization schemes on topographic processes (e.g., turbulent form drag, low-level flow blocking, and mountain waves) may also impact on the atmospheric circulation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Han et al () proposed a revised conversion rate of cloud water to rain water based on a cloud‐resolving simulation of a thunderstorm (Lim, ). They found that the conversion rate of cloud water to rain water decreases exponentially with height above the freezing level.…”
Section: Simulation Results and Model Improvementsmentioning
confidence: 99%
“…Thus, in order to improve the model simulation of subgrid‐scale wet scavenging, we added two modifications to the model. The first modification is adjusting the solubility of the tracer by introducing an ice retention factor, and the second modification is changing the conversion rate of cloud water to rain water by using the Han et al () scheme.…”
Section: Discussionmentioning
confidence: 99%
“…The physics package used here is similar to C2017 but with the advancement of computational cost and physical process. For example, the Rapid Radiative Transfer Model for GCMs scheme for shortwave and longwave radiation was improved in terms of computational cost (Baek, ), the Noah land surface model was upgraded from version 3.0 to the latest (version 3.4.1) with new surface input parameters (Koo et al, ), and the updated version of the simplified Arakawa‐Schubert convection scheme (Han et al, ; Kwon & Hong, ), which can be used in various model grids across gray‐zone resolutions, was used. In addition, a simple sea‐ice model was introduced with a newly created climatological data for ice thickness (Koo et al, ).…”
Section: Model Methods and Experimental Designmentioning
confidence: 99%